HAKIKAT PEMBANGUNAN HUKUM DAN PERTANGGUNGJAWABAN HUKUM DALAM PAYUNG PANCASILA PERSPEKTIF ISLAM - Paisol Burlian (State Islamic University North Sumatra, 2014)
Abstrak: Fokus tulisan ini mengkaji sejauhmana nilai filosofis tentang konsep rumusan norma pertanggungjawaban hukum memiliki kesamaan antara hukum Islam dengan nilai-nilai yang dicita-citakan pembangunan hukum nasional, yaitu terwujudnya nilai keadilan, kemanfaatan dan kemaslahatan hukum bagi manusia. Akan tetapi dalam hal rumusan batasan usia atau dewasa bagi seseorang untuk dapat memikul pertanggungjawaban hukum, terdapat beberapa perbedaan prinsip antara rumusan ‘âqil bâligh dalam hukum Islam dengan peraturan perundangan di Indonesia. Batasan usia dalam peraturan perundangan Indonesia perlu disesuaikan dengan kondisi sosial masyarakat dewasa ini. Ketercukupan asupan gizi, perkem- bangan teknologi rekayasa pangan, dan perkembangan teknologi informatika ber- pengaruh kuat terhadap kecenderungan lebih cepat dewasa bagi seseorang. Diharap- kan kajian ini dapat mengisi atau memberikan sumbangan konsep atau wawasan baru bagi tersusunnya ilmu hukum Indonesia atau pembangunan hukum nasional Indonesia.Abstract: The Essence Legal Development and its Accountability under the Banner of Pancasila in Islamic Perspective. The focus of this paper is to examine the the extent to which philosophical formulation of the concept of legal accountability norms are similar between Islamic law with the values aspired development of national laws, the final objective of which spins around the realization of the value of justice and for the interest of humans. However, in terms of the formulation of age limit for a person to be able to bear the legal liability, there are some differences between the formulation of the principle of legal capacity with the laws and regulations of Islamic law in Indonesia. The legal capacity in Indonesian laws needs to be formulated according to the social conditions of today’s society. Adequacy of nutrient intake, the development in food engineering technology, as well as information technology have relatively contributed to the process of maturity of a person become faster. This study is expected to fill the vacuum of law and throw new insights for the formulation and development of legal science in Indonesian national law.Kata Kunci: Pembangunan Hukum, Pertanggungjawaban Hukum, Pancasila dan Islam